2013
DOI: 10.2337/dc12-2455
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Complications and Mortality in Young-Onset Diabetes

Abstract: OBJECTIVETo evaluate long-term clinical outcomes and survival in young-onset type 2 diabetes (T2DM) compared with type 1 diabetes (T1DM) with a similar age of onset.RESEARCH DESIGN AND METHODSRecords from the Royal Prince Alfred Hospital Diabetes Clinical Database, established in 1986, were matched with the Australian National Death Index to establish mortality outcomes for all subjects until June 2011. Clinical and mortality outcomes in 354 patients with T2DM, age of onset between 15 and 30 years (T2DM15–30),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
255
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(294 citation statements)
references
References 22 publications
14
255
2
9
Order By: Relevance
“…Therefore, we believe that the more likely explanation is that young-onset type 2 diabetes represents a more severe form of diabetes. Our data support recently published studies suggesting that young-onset type 2 diabetes is the more lethal phenotype of diabetes and is associated with a greater mortality, more diabetes complications, unfavorable CVD risk factors, and greater difficulty in achieving glycemic control, even compared with type 1 diabetes (33)(34)(35)(36). Given the increasing incidence of young-onset type 2 diabetes and its severity, there is an urgent need for diabetes prevention efforts to be targeted toward youth.…”
Section: Comparison With the Literaturesupporting
confidence: 80%
“…Therefore, we believe that the more likely explanation is that young-onset type 2 diabetes represents a more severe form of diabetes. Our data support recently published studies suggesting that young-onset type 2 diabetes is the more lethal phenotype of diabetes and is associated with a greater mortality, more diabetes complications, unfavorable CVD risk factors, and greater difficulty in achieving glycemic control, even compared with type 1 diabetes (33)(34)(35)(36). Given the increasing incidence of young-onset type 2 diabetes and its severity, there is an urgent need for diabetes prevention efforts to be targeted toward youth.…”
Section: Comparison With the Literaturesupporting
confidence: 80%
“…The TODAY study, a large US multicentre randomised clinical trial comparing treatment options for 699 10-to 17-year-olds with type 2 diabetes, found that therapy based on current clinical practice guidelines [6] (metformin plus lifestyle intervention) was ineffective for maintaining glycaemic control in nearly 50% of participants after 1 year of treatment, despite 6 months of weekly face-to-face sessions [36]; hence, the TODAY study, together with the evidence for early diabetes-related complications [3,4], highlights the need for aggressive therapies that commence immediately or early after diagnosis. Bariatric surgery may be a feasible alternative, with one study demonstrating reversal of type 2 diabetes in ten of 11 adolescents [37].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of type 2 diabetes in young people is increasing in some populations [1,2], and the aggressive clinical course is evident [3,4]. Current treatment guidelines aim to optimise glycaemic control and prevent complications through lifestyle intervention with metformin therapy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…401 There is mounting evidence for a very high relative risk in younger individuals with type 2 DM (age ,40 years), 402 and additional guidance on care is needed. Except for glucose management, prevention of CVD follows the same general principles as for people without DM.…”
Section: A8 Diabetes Mellitus (Type 2 and Type 1)mentioning
confidence: 99%